2023
DOI: 10.3389/fnut.2023.1013503
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dairy consumption, physical activity, and blood pressure in Chinese young women

Abstract: IntroductionThe prevalence of hypertension (HTN) has been increasing in young adults. A healthy dietary pattern and increasing physical activity (PA) are commonly recommended as lifestyle modifications needed to manage blood pressure (BP). However, little is known about the relationship between dairy intake, PA, and BP in Chinese young women. The aim of this study was to examine whether BP was associated with dairy intake, moderate-to-vigorous intensity physical activity (MVPA) and total physical activity (TPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Similarly, in a large epidemiological study of Chinese adults, a significant association between a higher frequency of dairy consumption and reduced HTN was noted [ 9 ]. Higher intake of dairy was also reported to be associated with lower blood pressure levels in a sample of Chinese young women [ 10 ]. In addition, a study in China found that regular dairy consumption (≥ 4 days/week) was associated with a lower risk of ischemic heart disease (IHD) in males [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a large epidemiological study of Chinese adults, a significant association between a higher frequency of dairy consumption and reduced HTN was noted [ 9 ]. Higher intake of dairy was also reported to be associated with lower blood pressure levels in a sample of Chinese young women [ 10 ]. In addition, a study in China found that regular dairy consumption (≥ 4 days/week) was associated with a lower risk of ischemic heart disease (IHD) in males [ 11 ].…”
Section: Introductionmentioning
confidence: 99%